Knowledge and Attitudes with the Incidence of Hypertension - Lumastari Ajeng Wijayanti; Ririn Indriani; Glendy Ariando Salomon; Rina Asrina; Muhammad Purqan Nur; Suprapto Suprapto (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Hypertension is a condition characterized by systolic blood pressure ratings. Blood pressure reflects the resistance generated each time the heart beats and sends blood flow through the arteries, the highest record pressure generated by these contractions is called systolic pressure. The study aimed to determine the relationship between knowledge and attitudes with the incidence of hypertension. Quantitative research design with cross sectional study, with a sample of 76 subjects. The results of the chi square test obtained knowledge p-value=0,038, attitude= 0,003. It can be concluded that there is a relationship between people's attitudes and the incidence of hypertension. Community recommendations further improve counseling programs on hypertension and work with health workers with the community in prioritizing health services so that people prefer and determine a better and correct way of life.